Application of different Polyethylen glycole concentrations and evaluation of different methods for germination of alfalfa - Štrbanović Ratibor; Stanisavljević Rade; Đukanović Lana; Poštić Dobrivoj; Marković Jordan; Đokić Dragoslav; Dolovac Nenad (Journal on Processing and Energy in Agriculture, 2014)
This paper presents the germination three cultivars of alfalfa using different concentrations of PEG-6000 (Polyethylene glycol) and control. The aim of this study was to determine the tolerance of alfalfa under drought stress effects and the choice of optimal testing methods. Seed germination and establish the presence of hard seed alfalfa was done by the standard method without pretreatment and with pretreatment. Readout germination of alfalfa seeds was done after ten days, according to the Rules for testing seed quality of agricultural products. The concentration of PEG of 0.4 MPa has proven to be optimal for assessing the seed germination of alfalfa. The alfalfa cultivars have behaved differently towards different concentrations on PEG, indicating the possibility of correct selection of alfalfa cultivars for autumn sowing period (September) after seed harvest in August.